2015
DOI: 10.17219/acem/40399
|View full text |Cite
|
Sign up to set email alerts
|

Ileal Pouch Morphology and Microbiology in Ulcerative Colitis Patients

Abstract: Background. Ideal pouch created during restorative proctocolectomy is a new gastrointestinal organ -"neorectum". Although it is made from the ileum, it takes over function of the removed rectum. This new function results in significant morphological changes in pouch's mucous membrane, which becomes similar to the large bowel mucosa. The most common pathology of the ileal pouch is its inflammation -pouchitis. One of the suspected causes of pouchitis is bacterial flora disturbance. Objectives. The aim of the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
3
0
3
Order By: Relevance
“…Our research group found no difference between the present of S. aureus in faecal cultures in patients with chronic pouchitis compared to the Danish background population (data not published). Contradictory to the findings of Pawełka et al [ 32 ], Tannock et al reported a significantly lower number of Enterococcus spp ., Faecalibacterium prausnitzii , Clostridium spp ., Ruminococcus spp ., Eubacterium spp ., Lachnospiraceae and Insertae Sedis XIV in chronic pouchitis compared to healthy individuals, by use of faecal cultivation [ 33 ].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our research group found no difference between the present of S. aureus in faecal cultures in patients with chronic pouchitis compared to the Danish background population (data not published). Contradictory to the findings of Pawełka et al [ 32 ], Tannock et al reported a significantly lower number of Enterococcus spp ., Faecalibacterium prausnitzii , Clostridium spp ., Ruminococcus spp ., Eubacterium spp ., Lachnospiraceae and Insertae Sedis XIV in chronic pouchitis compared to healthy individuals, by use of faecal cultivation [ 33 ].…”
Section: Discussionmentioning
confidence: 91%
“…Another study by Pawełka et al found that chronic pouchitis or patients in need of long-term antibiotic treatment to control symptoms of pouchitis were associated with a significantly higher numbers of Staphylococcus aureus in faecal cultures [ 32 ]. Our research group found no difference between the present of S. aureus in faecal cultures in patients with chronic pouchitis compared to the Danish background population (data not published).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, subjects with pouchitis display decreased levels of Bacteroidetes [50,52,53], Lachnospiraceae [44,49], Ruminococcaceae [49], Streptococci [47,54], and Faecalibacterium [49], while incremented levels of Enterobacteriaceae (including E.Coli) [47,49] Fusobacterium [54,55], and Propionibacterium acnes [56] have been observed. Furthermore, Lim et al identified seventeen operational taxonomic units that were seen exclusively in subjects with inflamed pouches including Desulfosporosinus, Leptospira, Microcystis, Methylobacter, and Pseudoalteromonas [57], while Pawelka et al observed that the presence of Staphylococcus aureus correlated with a higher degree of chronic inflammation [58]. Ruminococcaceae and Lachnospiraceae have an important role in preserving the host's health due to their ability to hydrolyze starch and other sugars producing butyrate and other short-chain fatty acids (SCFAs), which are considered the principal nutrients of the colonic epithelial cells [59].…”
Section: Ipaa Microbiota and Pouchitismentioning
confidence: 99%
“…1, 2016 РЖГГК он-лайн -www.gastro-j.ru ков, выраженных в баллах. Диагноз паучита считается достоверным при сумме баллов 13 и более [17] [10]. Таким образом, мальабсорбция может быть рассмотрена как одна из составляющих возникновения диареи у наблюдавшейся пациентки.…”
Section: клинический разборunclassified